2014
DOI: 10.1126/scitranslmed.3007616
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 Attenuates Experimental Choroidal Neovascularization as a Potential Therapy for Wet Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is the most common form of central retinal blindness globally. Distinct processes of the innate immune system, specifically activation of the NLRP3 inflammasome, have been shown to play a central role in the development of both "dry" and neovascular ("wet") forms of the disease. We show that the inflammatory cytokine interleukin-18 (IL-18) can regulate choroidal neovascularization formation in mice. We observed that exogenous administration of mature recombinant IL-18 has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 27 publications
4
84
0
1
Order By: Relevance
“…Recent research has indicated that IL-18 is correlated with the development of GA, 13 whereas IL-18 could inhibit the formation of CNV in a laser-induced model. 59 In our research, we found that A2E could inhibit COX2-PGE2 pathways to impede the suppressive function of RPE cells in Th1-cell differentiation. This finding indicated that COX2-PGE2 pathways mediated regulatory function of RPE cells in Th1 immunity in vitro.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent research has indicated that IL-18 is correlated with the development of GA, 13 whereas IL-18 could inhibit the formation of CNV in a laser-induced model. 59 In our research, we found that A2E could inhibit COX2-PGE2 pathways to impede the suppressive function of RPE cells in Th1-cell differentiation. This finding indicated that COX2-PGE2 pathways mediated regulatory function of RPE cells in Th1 immunity in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…*P < 0.05, **P < 0.01, ***P < 0.001, ns P > 0.05. mediators of CNV; in the LA-induced RPE damage, the expression of NO and PGE2, together with their precursors COX2 and iNOS, were found increasing in a CNV model. 58,59 The controversy about the proinflammatory and immune modulatory functions of COX2-PGE2 pathways in AMD might be related to the complex pathological feature of different AMD lesions (CNV or GA), just as the paradox roles of IL-18 in CNV and GA. Recent research has indicated that IL-18 is correlated with the development of GA, 13 whereas IL-18 could inhibit the formation of CNV in a laser-induced model.…”
Section: Discussionmentioning
confidence: 99%
“…However, a conglomeration of five laboratories determined that this finding was in fact due to glycerol, a proangiogenic excipient in the IL-18 neutralizing antibody preparation (27). Subsequently, it was reported that recombinant murine IL-18 reduced choroidal neovascularization in a laser injury model (28). However, a multicentered study failed to reproduce those data, finding instead that IL-18 had no effect on CNV over 5-log dose range, and instead that IL-18 induced RPE degeneration (27), which has been independently corroborated (29).…”
Section: Discussionmentioning
confidence: 99%
“…5 The laser-induced CNV model was established as a highly reproducible model in nonhuman primates; however, its use in the mouse eye is less straightforward and appears susceptible to variability as highlighted by Poor et al 6 in a comprehensive study reported in 2014. Therefore, we assessed the efficacy response of mouse IL-18 (SB-528775; GlaxoSmithKline [GSK], Stevenage, UK) on the formation of neovascular lesions in the central region of the retinas of the recently described JR5558 mice, which develop bilateral spontaneous CNV and retinal angiomatous proliferation (RAP; Figs.…”
Section: Il-18 Prevents Spontaneous Neovascular Lesion Developmentmentioning
confidence: 99%